RELATIONSHIP OF AGE, MENOPAUSE STATUS, AND BMI WITH THE EVENT OF BACTERIAL VAGINOSIS IN NEW PATIENTS OF PELVIC ORGAN PROLAPSE - Atmi Marmiati; Pungky Mulawardhana; Zakiyatul Faizah (UNIVERSITAS AIRLANGGA, 2020)
AbstractBackground and Purpose : The prevalence of Bacterial Vaginosis (BV) among Asian women in India and Indonesia is 32% while in the case of BV in 2018 the obstetric clinic of Dr. Soetomo Regional Hospital is 181 BV sufferers. The impact of BV on Pelvic Organ Prolapse (POP) patients, namely the delay in POP treatment such as BV pessaries can be influenced by age, menopausal status, and BMI. This study aims to analyze the relationship of age, menopausal status, and BMI with the incidence of BV in POP patients. Methods: This study used observational analytics with a retrospective and cross sectional approach. The number of samples used was 86 patients. Samoel taking technique with total sampling. The independent variable is the incidence of BV, while the dependent variable is age, menopause status, BMI. Bivariate data analysis using chi square, fisher's exact test and multivariate test using multiple logistic regression tests. Results: The results showed a positive BV prevalence of 76.7% with the majority of patients aged over 60 years at 44.2%, having menopause at 81.4%, and having a BMI of 18.5-24.5 at 47.7%. Fisher's exact test analysis test showed p value of maternal age = 0.003 (RR = 6.398) and p value of BMI = 0.767 (p> 0.005). Chi square analysis test showed p value of menopause status = 0.009 (RR = 4.833). The multiple logistic regression analysis test showed that maternal age was the most dominant factor with a value of p = 0.006 (OR = 6.398 (1,711-23,929)). Conclusion: There is a relationship between age and menopausal status with the incidence of BV. Age is the most dominant independent factor in the incidence of BV.